PITFALLS IN AUTOPSY TISSUE SAMPLING - BANSOD, PRIYANKA; KALLA, ANAND RAJ; CHOYAL, MAHAVEER; KALLA, AMRIT RAJ (International Journal of Current Pharmaceutical Research, 2024)
Objective: To determine the pre-analytic factor which lead to autolysis in tissue sample thus hindering the establishment of histo-pathological cause of death in some autopsy tissue samples. Methods: Data collected from April, 2017 to September, 2018 (18 mo) at Department of Pathology, Dr. S. N. Medical College, Jodhpur. Results: The study, conducted over 18 mo from April 2017 to September 2018 at the Department of Pathology, Dr. S. N. Medical College, Jodhpur, analyzed 637 autopsy cases. These cases were predominantly from urban areas (70.17%), with a lesser number from rural regions (29.83%). A total of 698 tissue samples were received in various containers, with the majority (95.71%) preserved in formalin. The examination revealed that 38.4% of the samples were not autolysed, 36.1% were partially autolysed, and 25.5% were completely autolysed. The findings highlight a significant impact of the pre-analytic phase on tissue sample quality, notably the interval between death and autopsy, which was less than 24 h in 86.19% of cases, and the time from autopsy to histopathological examination, which ranged up to 1044 d. These factors were pivotal in the preservation status of the tissues, with formalin proving to be the most effective fixative in preventing autolysis, thus facilitating the accurate establishment of histopathological causes of death. Conclusion: If autopsy specimens are submitted for histopathological examination with proper protocol of transfer to fixative solution and transportation of tissue, this will help in determining the cause of death in majority of the autopsy specimens, therefore avoiding false negative results.